2019
DOI: 10.2147/opth.s184706
|View full text |Cite
|
Sign up to set email alerts
|

<p>Brolucizumab: evidence to date in the treatment of neovascular age-related macular degeneration</p>

Abstract: Age-related macular degeneration (AMD) is a global health concern and the leading cause of vision loss in the developed world. Intravitreal anti-vascular endothelial growth factor (VEGF) therapy has revolutionized the treatment of neovascular AMD, but there are still challenges with delivery of care and treatment burden with currently available medications. Brolucizumab is a single-chain antibody fragment inhibitor of all isoforms of VEGF-A. Its small molecular weight allows for high solubility and tissue pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 23 publications
0
48
0
Order By: Relevance
“…A seven-year review of 199 endophthalmitis cases by Sachdeva et al found that 8.5% of cases at a tertiary referral academic center followed anti-VEGF injections [ 81 ], while Gupta et al found anti-VEGF injections accounted for 11% of their cases [ 82 ]. Infectious endophthalmitis has been reported with all available anti-VEGF agents, and its frequency does not differ significantly by drug [ 77 , 83 , 84 , 85 ].…”
Section: Infectious Endophthalmitismentioning
confidence: 99%
“…A seven-year review of 199 endophthalmitis cases by Sachdeva et al found that 8.5% of cases at a tertiary referral academic center followed anti-VEGF injections [ 81 ], while Gupta et al found anti-VEGF injections accounted for 11% of their cases [ 82 ]. Infectious endophthalmitis has been reported with all available anti-VEGF agents, and its frequency does not differ significantly by drug [ 77 , 83 , 84 , 85 ].…”
Section: Infectious Endophthalmitismentioning
confidence: 99%
“…However, despite the clinical use of numerous anticancer therapeutic antibodies, a limited number of their therapeutic targets, including CD20, vascular endothelial growth factor-A (VEGF-A), epidermal growth factor receptor (EGFR), human epidermal growth factor receptor 2 (HER2), programmed cell death protein-1 (PD-1), and programmed death-ligand 1 (PD-L1), have currently been identified [ 21 , 22 , 23 , 24 , 25 ]. Some examples include ofatumumab, ocrelizumab, ibritumomab tiuxetanand, and rituximab for CD20-targeted mAbs; bevacizumab, ranibizumab, and brolucizumab for VEGF-A-targeted mAbs; cetuximab, panitumumab, and necitumumab for EGFR-targeted mAbs; trastuzumab, and pertuzumab for HER2-targeted mAbs; nivolumab, pembrolizumab, and cemiplimab for PD-1-targeted mAbs; lastly, atezolizumab, avelumab, and durvalumab for PD-L1-targeted mAbs [ 21 , 22 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]. As such, identifying novel therapeutic targets and understanding the molecular mechanism of metastatic cancer cells are essential for overcoming unmet medical needs in current cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Two reviews on brolucizumab and the visual, anatomic, and safety outcomes from the key clinical trials were recently published [14, 28, 29]. Here, we summarize the main milestones in the clinical development of brolucizumab, outlining the rationale and role of these key studies, and briefly conclude with the Phase IIIa and b clinical outlook for this agent.…”
Section: Clinical Evidence Of Brolucizumab Usementioning
confidence: 99%
“…Aside from anti-VEGFs, other innovative approaches to treatment or delivery, e.g., gene therapy or the development of long-acting drug delivery systems, also hold promise for the management of this disease [8, 14].…”
Section: Introductionmentioning
confidence: 99%